Synthesis and Crystal Structure of a Copper(II) Benzoate Complex Bearing a Bis-2,2′-Tetrahydrofuryl Peroxide Moiety - Solera Rojas, José Andrés (2018)
Complex [Cu2(ben)4·2THF−(η1–O2)]∞ (2) (ben=C6H5CO2− benzoate; THF=tetrahydrofuran) was isolated when a solution of Cu2(ben)4·2THF (1) in THF upon natural sunlight irradiation yields crystals suitable for single-crystal X-ray diffraction analysis. 2, crystallized in the C2/c monoclinic space group, Z=8, V=3394.2 (4) Å3, and the unit cell parameters a=9.7935(7) Å, b=19.0055 (13) Å, c=18.2997 (13) Å, α=90°, β=94.7996 (11)º and γ=90°. This is the first example of a polymeric copper(II) carboxylate compound stabilizing a peroxo group via its apical ligand (THF molecule). Additionally, 2 was also characterized by elemental analysis, Fourier-transformed infrared spectroscopy (FTIR) and Raman spectroscopy